Design and Analysis of a Reconfigurable Gilbert Mixer for Software-Defined Radios - Mehta, S; Li, X; Donelli, M (MDPI AG, 2021)
A reconfigurable gm-boosted, image-rejected downconversion mixer is presented in this paper using the SiGe 8 HP technology. The proposed mixer operates within 0.9–13.5 GHz that is suitable for software-defined radio applications. The conversion mixer comprises of resistive biased radio frequency (RF) section, double balanced Gilbert cell mixer core sections divided as per I and Q stages for image-rejection purpose, inductively peaked gm-boosting section and tunable filter section, respectively. In comparison to previous works in the scientific literature, the design shows enhanced conversion gain (CG), noise figure (NF), and image-rejection ratio (IRR). For the entire band of operation, the mixer attains a good return loss |S11| of <−10 dB. Additionally, the design accomplishes an excellent CG of 22 dB, NF of 2.5 dB, and an image-rejection ratio of 30.2 dB at maximum frequency. Finally, a third-order intercept point (IP3) of −3.28 dBm and 1 dB compression point (CP1) of −13 dBm, respectively, shows moderate linearity performance.
Keywords: Software-defined radio; Mixer; Image-rejection ratio; Impedance matching